PERSONAL BRANDING PEJABAT PUBLIK (ANALISIS ISI AKUN INSTAGRAM WALIKOTA SOLO GIBRAN RAKABUMING RAKA) - Sekar Putri (MEDIOVA: Journal of Islamic Media Studies, 2021)
: The main focus of this research on personal branding of Solo Mayor Gibran Rakabuming Raka through his instagram account, the reason for analyzing Gibran's instagram account is because he is a public official who was recently elected as mayor of Solo and his figure is often a conversation because it is the son of the President of the Republic of Indonesia, Joko Widodo. However, research will be directed about the personal branding of the mayor of Solo since he ran for Mayor of Solo until he was appointed as Mayor of Solo and how he created a great personal branding. The research method used is Qualitative Content Analsis. The results showed that Gibran Rakabuming is identical to Jokowi's figure as in blusukan activities, gestures, word selection and other attributes, but he presents himself to look different from the father of President Jokowi such as blusukan style with a bicycle named mider praja and has a focus of work programs such as in this pandemic era, he focused on the work program that became the tagline "KEBUT VAKSINASI KEBUT PEMULIHAN EKONOMI" Keywords: Content Analysis, Instagram, Personal Branding, Public Officials